Snow cover variability in the Himalayan–Tibetan region. (8th April 2013) - Singh, S. K.; Rathore, B. P.; Bahuguna, I. M.; Ajai
ABSTRACT Snow cover in the Himalayan–Tibetan region is highly variable in space and time, and influences the hydrology and climate at regional and global scales. Monthly MODIS snow cover and land surface temperature (LST) data have been analysed for the period 2000–2011. The details of the snow cover pattern during accumulation and ablation has been studied for the Indus, Ganga and Brahmaputra river basins. These river basins have shown a unique pattern of snow accumulation and ablation. The Indus and Ganga Basins have shown high snow cover percentage than the Brahmaputra during ablation period. The maximum snow cover for the three basins altogether is approximately 85% of the total geographic area which reduces to approximately 10% during ablation. Accumulation and ablation variations are clearly depicted by the LST variations of the respective basins. However, the Indus Basin has shown a unique increasing trend in snow cover, whereas the Ganga and Brahmaputra Basins have shown no significant trend in this decade. Snow cover for Tibetan region during March (accumulation) and September (ablation) months have not shown either increasing or decreasing trend from 2000 to 2011. Analysis of monthly average basin LST data has shown that Indus Basin experiences subfreezing conditions and delay in rise of peaks in comparison to Ganga and Brahmaputra which shows high LST during accumulation. This study shows that the Indus, Ganga and Brahmaputra Basins have shown different patterns in the snow cover variations during the last 12 years.